Smashing the crystal ball: post-structural insights associated with contemporary anarchism and the revision of blueprint utopianism - Alexander, Tarryn Linda (Rhodes University, Faculty of Humanities, Department of Sociology, 2012)
This thesis is an exploration of the images which define revolution's meaning. It suggests a possible shifting of emphasis from the scientific imaginary which centres on identifying the correct way to totalising revolution, towards a post-structuralist-anarchistic imaginary which privileges prefigurative radicalisations of social relations in the here and now. It looks specifically at how the field of post-structuralism intertwines with historically anarchist concepts to generate an horizon of social change animated by experimental and open-ended transformations. While the thesis offers positive characterisations of the types of contemporary movements, tactics and principles which embody the change from closed to open utopianism, it is chiefly a commentary on the role of theory in depicting the complexity of relations on the ground and the danger of proposing one totalising pathway from one state of society to another. It asks the reader to consider, given the achievements of movements and given the insights of post-structuralism, whether it is still worthwhile to proclaim certainty when sketching the possibilities for transcendence toward emancipation, an aim, which in itself, is always under construction. I engage this by firstly establishing a practical foundation for the critique of endpoints in theory by exploring the horizontal and prefigurative nature of a few autonomous movements today. Secondly I propose the contemporary theory of post-structuralist anarchism as concomitant with conclusions about transformation made in the first chapter. Finally I recommend a few initial concepts to start debate about the way forward from old objectivist models of transformation. The uncertainties of daily life, crumbling of economic powers and rapid pace of change in the twenty-first century have opened up fantastic spaces for innovative thought. Reconsidering old consensus around what constitutes a desirable image of revolution is of considerable importance given today's burgeoning bottom-up political energy and the global debate surrounding the possibilities for bottom-up revolutionisation of society. I submit that theories which portray stories of permanent, pure and natural end-points to revolution are deficient justifications for radical action.
Keywords: Social change; Utopian socialism -- Philosophy; Utopias -- Philosophy; Anarchism